Sex Differences in (+)-Amphetamine- and (+)-Methamphetamine-induced Behavioral Response in Male and Female Sprague-Dawley Rats - Milesi-Hallé, Alessandra (2007)
(+)-Methamphetamine (METH) and (+)-amphetamine (AMP) are structurally similar drugs that are reported to induce similar pharmacological effects in rats of the same sex. Because pharmacokinetic data suggest female rats should be more affected than males, the current studies sought to test the hypothesis that the behavioral and temporal actions of METH and AMP should be greater in female Sprague-Dawley rats than in males. Using a dosing regimen designed to reduce the possibility of tolerance and sensitization, rats were administered 1.0 and 3.0 mg/kg intravenous drug doses. Distance traveled, rearing events and focal stereotypies (e.g., head weaving, sniffing) were measured. Female rats traveled significantly greater distances and displayed a greater number of rearing events than males after both doses. Analysis of stereotypy ratings after 3.0 mg/kg revealed that focal stereotypies were more pronounced and lasted longer in females. The second study compared the potencies of METH and AMP in inducing locomotor activity and focal stereotypies in each sex. No differences in potency were found when METH and AMP effects were compared within males or females. In summary, these studies showed female rats displayed greater and longer-lasting locomotor activity and more stereotypic behaviors, supporting earlier evidence of significant sexual dimorphism in pharmacokinetics.